Pengaruh Motivasi Kerja dan Kepuasan Kerja terhadap Organizational Citizenship Behavior (OCB) pada Guru PPPK SMAN XYZ Bandung - Meirani Purnama, Kaisya; Khaerul Rizal Abdurahman (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to determine the effect of work motivation and job satisfaction on organizational citizenship behavior (OCB) among Government Employees with Work Agreements (PPPK) teachers at SMAN XYZ Bandung. The research method used was a quantitative approach with an associative approach. Data were collected through questionnaires distributed to 32 respondents and analyzed using SPSS version 23, using validity, reliability, classical assumptions, multiple linear regression, and t- and F-tests. The results indicate that PPPK teachers' work motivation and job satisfaction are in the high category and have a positive effect, both partially and simultaneously, on organizational citizenship behavior. The t-test indicates that work motivation and job satisfaction each have a significant effect on OCB, while the F-test shows that both together have a significant effect, with a determination value of 85.5%. The conclusion of this study is that the higher the teacher's motivation and job satisfaction, the higher the organizational citizenship behavior, demonstrated in the form of loyalty, responsibility, and active participation in school progress.   Keywords: Work Motivation, Job Satisfaction, Organizational Citizenship Behavior, PPPK Teachers